A philosopher looks at science - Cartwright, Nancy 1944- (Cambridge University Press, 2022)
"Three common images of science, widely shared alike by philosophers, scientists and people in general : 1) science = theory + experiment, 2) it's all physics really, 3) science is deterministic : it says that what happens next follows inexorably from what happened before. This book paints, one-by-one, alternative pictures to these three standard images of science "--
Includes bibliographical references and index
Keywords: Wissenschaftsphilosophie; Philosophie; Aussagekraft; Wissenschaftstheorie; Science / Philosophy; SCIENCE / Philosophy & Social Aspects